Transgender Rights and Debate from an Islamic Legal Perspective - Prof. Dr. Khalid Sultan; Dr. Hafiz Hasan Madni; Dr. Shakeela Ibrahim; Dr. Shamaila Athar (Al-Qanṭara, 2023)
This research study explores the complex relationship between transgender rights and Islamic legal ideas, providing insight into the changing discourse regarding gender identity within Islamic jurisprudence. This study investigates the religious and legal aspects of the ongoing dispute surrounding the rights, social recognition, and discrimination experienced by transgender individuals residing in predominately Islamic nations. This study aims to enhance scholarly comprehension of transgender rights within Islamic contexts by conducting a thorough examination of Islamic literature, historical precedents, and contemporary interpretations. The initial segment of the paper explores the theological discourse present within the realm of Islamic studies. This study investigates the perspective of traditional Islamic law on gender identity and its capacity to include modern interpretations pertaining to transgender individuals. The research underscores a range of theological perspectives, placing particular emphasis on the dynamic development of Islamic discourse on gender diversity. The subsequent section of the study delves into an examination of the legal entitlements afforded to transgender individuals in specific Islamic nations, namely Iran and Pakistan by means of two illustrative case studies. The cases mentioned above exemplify the various methodologies employed in addressing transgender rights within the context of Islamic legal frameworks. It acknowledges the existence of diverse interpretations and practices pertaining to this issue across various nations with Muslim-majority populations.